Definitions of neonatal abstinence syndrome in clinical studies of mothers and infants: an expert literature review - Jilani, Shahla M.; Jordan, Chloe J.; Jansson, Lauren M.; Davis, Jonathan M. (Journal of perinatology, 2021)
Neonatal abstinence syndrome (NAS) results from discontinuation of in utero exposures to opioids/substances. The rising incidence of NAS has prompted an increased need for accurate research and public health data. To examine how NAS has been defined in clinical studies of opioid-exposed mothers and infants, a review process was developed based on the RAND/UCLA Appropriateness Method, yielding 888 abstracts. Per inclusion criteria, 57 abstracts underwent full-text review. To define NAS, studies cited using modified versions of the Finnegan NAS scoring tool ( n = 21; 37%), ICD-9/10 coding ( n = 17; 30%), original Finnegan tool ( n = 16; 28%), Eat Sleep Console ( n = 3; 5%), and Lipsitz ( n = 3; 5%) tools, (3 cited 2+ tools). Most studies utilized subjective NAS scoring/assessment algorithms and neonatal coding as key elements defining NAS. While most cited opioid exposure as integral to their inclusion criteria, 26% did not. These approaches highlight the need for a more refined and standardized definition of NAS.